Effectiveness of menstrual hygiene management training to enhance knowledge, attitude, and practice among adolescents in Sindhupalchowk, Nepal. - Swastika Shrestha; Saki Thapa; Bikram Bucha; Safal Kunwar; Bigyan Subedi; Aishwarya Rani Singh; Durga Datta Chapagain; Raghu Dhital; Maxine Caws (PLoS ONE)
Background Menstrual Health (MH) knowledge, attitude and practice (KAP) are highly affected by access to information regarding menstruation. Despite being included in the school curriculum, Sexual and Reproductive Health (SRH) education is often not delivered in practice. School-based educational interventions have been shown to be effective in promoting MH. Methods A school-based study was conducted in Indrawati rural municipality of Sindhupalchowk district in Nepal. 427 participants (175 boys and 252 girls), aged 11-13, completed a questionnaire evaluating MH KAP before receiving a structured training module on MH provided by experienced trainers from Putali Nepal using the Menstrupedia tool. The questionnaire was repeated one month after the training. Pre and post intervention scores were compared to determine the effect of the intervention. Focus group discussions were also conducted to understand the perceptions of participants toward SRH teaching. Association of independent socio-demographic with dependent variables knowledge and attitude towards menstrual health were analyzed using MANOVA test. The Wilcoxon signed-rank test was used to compare the median outcome of the pre and post-test attitude and knowledge. The maximum possible score was 6 for MH knowledge. The total attitude score ranged 14 to 70. Results The median knowledge score increased by 1 point (p = <0.001) and the median attitude score by 5 points (p = <0.001), one month after delivery of the intervention. Higher knowledge scores were significantly associated with Hindu religion, female gender, higher father's literacy, and mothers in an informal occupation on multivariate analysis. Higher attitude scores were significantly associated with Hindu religion while lower attitude scores were associated with a mother in an informal occupation. Conclusion The Menstrupedia comic educational intervention improved knowledge and attitude towards menstruation among Nepali adolescents. A scale-up of the Menstrupedia based intervention would significantly change knowledge and attitude towards menstruation in Nepali adolescents.